Changes in the soil and rhizosphere microbiomes associated with bacterial wilt decline in the tomato monoculture field - Junwei Peng; Jinfeng Hou; Hong Liu; Dmitri V. Mavrodi; Olga V. Mavrodi; Feifei Sun; Minchong Shen; Xia Wang; Keke Dang; Min Yan; Hui Liang; Yuanhua Dong; et al. (Geoderma)
Monoculture farming streamlines field equipment use and increases the efficiency of planting and harvesting, but at the same time, exacerbates the severity of soilborne diseases. Disease-suppressive soils are an effective and sustainable resource for managing soilborne diseases in monoculture systems. However, the evolution and mechanisms of soil suppressiveness remain elusive, limiting the broader acceptance of suppressive soil in agriculture. This study investigated changes in the belowground tomato microbiome during long-term monoculture leading to an outbreak and subsequent suppression of bacterial wilt, a destructive soilborne disease. The wilt incidence steadily increased, culminating in the most severe outbreak in the fifth cropping cycle. Surprisingly, in the seventh crop, wilt symptoms spontaneously declined, signifying a transition toward the disease-suppressive state. This transition involved the enrichment of Streptomyces and trace elements (Mn, Ni) in the bulk soil, accompanied by increased diversity and abundance of Pseudomonas in the rhizosphere. Greenhouse disease assays confirmed that the suppressive soil had significantly lower wilt incidence and shaped a healthy rhizosphere community characterized by reduced prevalence of pathogenic taxa and greater resource utilization diversity, compared to its disease-conducive counterpart. Moreover, functional analysis of the suppressive rhizosphere metagenome revealed enrichment of genes for the synthesis of antibiotics, polysaccharides, nitrogen metabolism, mineral absorption, and energy production. Drenching tomato seedlings with suppressive rhizosphere soil suspensions enriched beneficial rhizosphere microorganisms such as Pseudomonas and Bacillus, improving plant growth and physiological characteristics compared to seedlings treated with conducive rhizosphere soil suspensions. Furthermore, Pseudomonas and Bacillus were isolated and validated for their antagonistic ability against R. solanacearum, demonstrating their inhibitory effect on bacterial wilt in greenhouse trials. This study is among the first to directly demonstrate that long-term tomato monoculture can induce specific soil suppressiveness against Ralstonia wilt, while also revealing the key changes in soil and rhizosphere microbiomes and their function associated with this phenomenon.